Testing the boundaries of lean thinking: observations from the legal public sector - Hines, P.; Martins, A. L.; Baile, J. (Public Money and Management, 2008)
This article explores how Lean Thinking can be successfully extended into the legal sector, which in most advanced economies is dominated by the public sector. Two public sector cases from Portugal and Wales are discussed. The authors look at where and how implementation of Lean Thinking might start, and the modifications required to do this successfully. A tentative Lean legal supply chain model which will take three to five years to implement is presented.